Let us dream the path to a better future - Francis, Pope. (New York Simon & Schuster, 2020)
"In this revelatory, uplifting, and practical book, the preeminent spiritual leader explains why we must-and how we can-make the world safer, fairer, and healthier for all people now
Keywords: Pope Francis